Pemberdayaan Kerang Taruna Melalui Pelatihan Teknik Penanaman Hidroponik di Desa Sukoanyar Kecamatan Mojo Kabupaten Kediri - Rhohman, Fatkur; Istiqlaliyah, Hesti; Yasinta Sindy; M. Muslimin Ilham; Nuryosuwito (Universitas Nusantara PGRI Kediri, 2021)
Sukoanyar Village is one of the villages located in the southern part of Kediri Regency, Sukoanyar Village is located in Mojo District. Sukoanyar Village Community Most of the residents are farmers, but not all of them have private land, meaning that the majority of them work on other people's gardens, or the